PERSEPSI GURU NON PENJASORKES TERHADAP KOMPETENSI GURU PENJASORKES - ., Atias; ., Imran; ., Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: Research on teacher non Penjasorkes on teacher competencePenjasorkes first middle school level as sub Jagoi Babang Bengkayang. Study is asurvey technique with questionnaires or questionnaire, which consists of four datacollection item that personal competence, pedagogic competence, professionalcompetence, and social competence and questionnaire used consists of 40questions. Based on the results of research known as much as 69.2% stated thatteachers' competence Penjasorkes medium category, 30.8% stated Penjasorkesteacher competence is very low, 0% said low Penjasorkes teacher competence andteacher competence 0% said Penjasorkes including high category. Then concludedmost of the non Penjasorkes teachers' perceptions of the competence of a teacherPenjasorkes Jagoi Babang districts included in the medium category (69.2%) ".Keywords: Perception, Competencies, Master Penjasorkes.Abstrak: Penelitian tentang guru non Penjasorkes terhadap kompetensi guruPenjasorkes tingkat sekolah menegah pertama se-kecamatan Jagoi BabangKabupaten Bengkayang. Penelitian yang digunakan adalah survei dengan teknikangket atau kuesioner, dimana pengambilan data terdiri dari empat item yaitukompetensi kepribadian, kompetensi paedagogik, kompetensi profesional, dankompetensi sosial dan angket yang digunakan terdiri dari 40 pertanyaan.Berdasakan hasil penelitian diketahui sebanyak 69,2% menyatakan kompetensiguru penjasorkes kategori sedang, 30,8% menyatakan kompetensi gurupenjasorkes rendah sekali, 0% menyatakan kompetensi guru penjasorkes rendahdan 0% menyatakan kompetensi guru penjasorkes termasuk kategori tinggi. Makadisimpulkan sebagian besar persepsi guru non Penjasorkes terhadap kompetensiguru Penjasorkes se-kecamatan Jagoi Babang termasuk dalam kategori sedang(69,2%).Kata kunci : Persepsi, Kompetensi, Guru Penjasorkes.